PENGARUH BERBAGAI KONDISI PREPARASI DAN PENYIMPANAN SUSU FORMULA PADA PERTUMBUHAN SPORA Bacillus cereus DAN Clostridium perfringens [The growth of Bacillus cereus and Clostridium perfringens spores under a variety of preparation and storage condition] - Purwanti Maya; Mirnawati Sudarwanto; Winiati P. Rahayu; A. Winny Sanjaya (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2009)
The aim of this study was to evaluate the ability of Bacillus cereus and Clostridium perfringens spores to survived in different preparation temperature (25, 35, and 70°C for B. cereus and 25, 45, 70ºC for C. perfringens) and modified storage condition (with 50 and 75% humidity; opened, closed and opened twice a day during period of observation) of powdered milk formula. The spores of B. cereus ATCC 13061 and C. perfringens CP-1 artificially contaminated to the milk formula. Results showed that B. cereus and C. perfringens spores were germinated and growth in reconstituted milk formula. Bacteria population increased ≥1 log within 3 hours at room temperature (28-29ºC). The spores of both bacteria survived from dry condition of powdered milk formula, like when aw of the formulas increased cause of storage condition.